Spatial Aglomeration of Firms - Theory and Application for Industrial District 22@ of Barcelona - Yuri Yegorov; Oscar Mascarilla-i-Miro (European Regional Science Association (ERSA), 2005)
The goal of this paper is theoretical analysis of the complex process of agglomeration of firms in space when cities are also competing for them. Positive spillovers tend firms to locate in the same area, while congestion effects limit this process. Thus, for any given city there exists an optimal number of firms. If there are fewer firms, we face competition under increasing returns to scale, with path dependence effects, described by W.B.Arthur (1994). Hence, if firms are relatively scarce, not all cities would be occupied by firms at optimal level. The problem of a firm is to choose an optimal city expecting rational behaviour of other firms. Such factor as office rent depend on city size, while wage cost and spillover effects depend also on the number of firms there. Firms choose to agglomerate in those cities where after optimal entry their profits will be maximized. Under certain conditions for parameter set, there exists an equilibrium allocation, where all firms are located in the cities with better parameters. Since cities are different, their attractiveness also differ. At present, London is the leader in attractiveness among European cities, while Barcelona, stays at the 7th position (Healey and Baker, 2001). But this situation is unstable and depends on city development. On empirical side, we analyse the potential effect of investment in infrastructure in Barcelona to improve its attractiveness.
Keywords: 330